2001
DOI: 10.1177/01461672012711009
|View full text |Cite
|
Sign up to set email alerts
|

Intensity Bias in Affective Forecasting: The Role of Temporal Focus

Abstract: In five studies, university students predicted their affective reactions to a wide variety of positive and negative future events. In Studies 1 to 3, participants also reported the affective reactions they experienced when the target event occurred. As hypothesized, they tended to anticipate more intense reactions than they actually experienced. In Studies 3 to 5, a cognitive determinant of this “intensity bias” was examined. It was hypothesized that people anticipate stronger affective reactions when they foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
156
2
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(177 citation statements)
references
References 29 publications
12
156
2
3
Order By: Relevance
“…This impact bias-the tendency of people to overestimate the emotional impact of future events on their lives-has received ample empirical support. For example, it has been shown that romantic partners overestimate how bad they feel if their relationship ends, football fans overestimate their happiness after their team won a game, college students overestimate their negative emotions if they would be assigned to an ''undesirable'' dormitory, people gambling with money overestimate how unhappy they feel when they lose, professors overestimate their positive emotions following a positive tenure decision, and people taking their driver's license exam overestimate their disappointment after failing the exam (Dunn, Wilson, & Gilbert, 2003;Finkenauer, Gallucci, Van Dijk, & Pollmann, 2007;Gilbert, Pinel, Wilson, Blumberg, & Wheatley, 1998;Kermer, Driver-Linn, Wilson, & Gilbert, 2006;Wilson, Wheatley, Meyers, Gilbert, & Axsom, 2000; see also Buehler & McFarland, 2001;Gilbert, Gill, & Wilson, 2002;Gilbert, Lieberman, Morewedge, & Wilson, 2004;Gilbert, Morewedge, Risen, & Wilson, 2004;Loewenstein & Schkade, 1999;Sanna & Schwarz, 2004;Wilson, Meyers, & Gilbert, 2001.…”
Section: Affective Forecasting and The Impact Biasmentioning
confidence: 99%
“…This impact bias-the tendency of people to overestimate the emotional impact of future events on their lives-has received ample empirical support. For example, it has been shown that romantic partners overestimate how bad they feel if their relationship ends, football fans overestimate their happiness after their team won a game, college students overestimate their negative emotions if they would be assigned to an ''undesirable'' dormitory, people gambling with money overestimate how unhappy they feel when they lose, professors overestimate their positive emotions following a positive tenure decision, and people taking their driver's license exam overestimate their disappointment after failing the exam (Dunn, Wilson, & Gilbert, 2003;Finkenauer, Gallucci, Van Dijk, & Pollmann, 2007;Gilbert, Pinel, Wilson, Blumberg, & Wheatley, 1998;Kermer, Driver-Linn, Wilson, & Gilbert, 2006;Wilson, Wheatley, Meyers, Gilbert, & Axsom, 2000; see also Buehler & McFarland, 2001;Gilbert, Gill, & Wilson, 2002;Gilbert, Lieberman, Morewedge, & Wilson, 2004;Gilbert, Morewedge, Risen, & Wilson, 2004;Loewenstein & Schkade, 1999;Sanna & Schwarz, 2004;Wilson, Meyers, & Gilbert, 2001.…”
Section: Affective Forecasting and The Impact Biasmentioning
confidence: 99%
“…Existing studies on mathematics anxiety have predominately used the less costly and more convenient trait assessment method (Wilhelm, Perrez, & Pawlik, 2011). However, in comparison with scores obtained by multiple state assessments, which are regarded as reflecting actual emotions as they are experienced (Robinson & Clore, 2002), trait assessments of emotions are generally overestimated (Buehler & McFarland, 2001). It has been argued that the discrepancy between trait and state measures of emotions (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The trait-state discrepancy in anxiety and the role of academic self-concept The discrepancy between trait and state self-reports of emotion (referred to from here on as the trait-state discrepancy) reflects the observation that trait emotions are usually overestimated in comparison with state emotions (also termed sometimes as intensity bias; Buehler & McFarland, 2001). In their accessibility model of emotional self-report, Robinson and Clore (2002) postulated that subjective beliefs play an important role in the trait-state discrepancy.…”
Section: Introductionmentioning
confidence: 99%
“…In the past several decades, psychologists and behavioral decision theorists have accumulated ample evidence showing that people often over-predict the intensity or duration of their future affective reaction, a phenomenon called the impact bias (Gilbert, Driver-Linn, & Wilson, 2002;. Here, we follow Wilson and Gilbert (2003) to use "impact bias" to refer to both intensity bias (e.g., Buehler & McFarland, 2001) and durability bias (Gilbert, Pinel, Wilson, Blumberg, & Wheatley, 1998).…”
Section: Impact Biasmentioning
confidence: 99%